Arbuscular mycorrhiza‐specific enzymes FatM and RAM2 fine‐tune lipid biosynthesis to promote development of arbuscular mycorrhiza. Issue 4 (5th April 2017) - Bravo, Armando; Brands, Mathias; Wewer, Vera; Dörmann, Peter; Harrison, Maria J.
Summary: During arbuscular mycorrhizal symbiosis (AMS), considerable amounts of lipids are generated, modified and moved within the cell to accommodate the fungus in the root, and it has also been suggested that lipids are delivered to the fungus. To determine the mechanisms by which root cells redirect lipid biosynthesis during AMS we analyzed the roles of two lipid biosynthetic enzymes (FatM and RAM2) and an ABC transporter (STR) that are required for symbiosis and conserved uniquely in plants that engage in AMS. Complementation analyses indicated that the biochemical function of FatM overlaps with that of other Fat thioesterases, in particular FatB. The essential role of FatM in AMS was a consequence of timing and magnitude of its expression. Lipid profiles of fatm and ram2 suggested that FatM increases the outflow of 16:0 fatty acids from the plastid, for subsequent use by RAM2 to produce 16:0 β‐monoacylglycerol. Thus, during AMS, high‐level, specific expression of key lipid biosynthetic enzymes located in the plastid and the endoplasmic reticulum enables the root cell to fine‐tune lipid biosynthesis to increase the production of β‐monoacylglycerols. We propose a model in which β‐monoacylglycerols, or a derivative thereof, are exported out of the root cell across the periarbuscular membrane for ultimate use by the fungus.